196k views
4 votes
Apply the distributive property to create an equivalent expression.

(7−4n)⋅6= ?

User Mluker
by
6.5k points

2 Answers

6 votes

Answer:

(7 - 4n) · 6 = 42 - 24n

Explanation:

The distributive property: a(b - c) = ab - ac

(7 - 4n) · 6 = (7)(6) - (4n)(6) = 42 - 24n

User Felix
by
6.9k points
5 votes

−24n+42

Let's apply the distributive property to create an equivalent expression:

(7−4n)⋅6

Steps to solve:

1. Rearrange terms:

(−4n+7)⋅6

2. Re-order terms so constants are on the left:

6(−4n+7)

3. Distribute:

−24n+42

Answer:

−24n+42

User Ndberg
by
5.9k points